Aggression towards helping professions: violence as communication, listening as prevention? - Sicora, Alessandro (Argumentum, 2014)
The rise in numbers of the episodes of aggression in health and social services arouses concern on how prevention programs can be planned and implemented. There are several forms of violence and the categories verbal/physical, active/passive, direct/indirect help to describe a multidimensional phenomenon involving organizational aspects, psychological and social factors, gender issues, as well as components related to law, architecture and other fields of study. If violence is considered communication, listening is the best form of prevention. The analysis of the organization and the continuous effort toward reflective practice on aggressions are crucial to understand and prevent such acts. This article proposes some tools, in the form of key questions, to support these activities.